ANALISIS PENYALURAN ZAKAT PROFESI DOSEN PADA PROGRAM BANTUAN UANG KULIAH TUNGGAL MAHASISWA DALAM PEMBERDAYAAN DI BIDANG PENDIDIKAN - Sonia Rosta Alannawa; Maulida Draseva Angela; M. Thoriq Farchan; Bakhrul Huda (Program Studi Ekonomi Syariah IAI Darul Ulum Kandangan, 2023)
This research aims to analyze how professional zakah is distributed in the UINSA Zakah Management Unit (UPZ) program as an effort to empower the economics of UINSA students. This research uses a qualitative approach method using descriptive analysis by directing researchers to the conditions to be studied and reviewing related literature. The data used in this research were obtained through observation and interviews and the data were analyzed using the triangulation method. The research results show the mechanism for distributing professional zakah in the UINSA Zakah Management Unit (UPZ) program as an effort to empower the economics of UINSA students and also explains data on zakah that has been distributed over the last 3 years. There are also obstacles found in the distribution of professional zakah funds. Such as the lack of interest of lecturers to participate in providing professional zakah funds to UPZ UINSA, mechanisms that must involve contributions from several parties, to the lack of precise distribution of funds according to the schedule set by UPZ UINSA, and obstacles in equalizing the amount of funds given to students. To deal with these obstacles, several solutions have been put forward, such as attracting the interest of lecturers or employees at UPZ UINSA, an understanding approach is needed for them which must be carried out by UPZ UINSA, providing appropriate learning or direction to students who wish to register for UKT assistance so that they do not Several errors have caused problems in the performance of UPZ UINSA, and more explanation or understanding is needed for professors who have channeled their professional funds to UPZ UINSA for changes in student targets and more appropriate amounts of aid funds so that they feel more useful.